Nudging businesses to pay their taxes - Mathias Sinning; Katja M. Fels (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
Reminders and a simplified language help tax authorities to collect outstanding tax payments more efficiently. - Tax noncompliance harms both social cohesion and public welfare. In the US alone, tax underpayment averaged 39 billion per year from 2008 to 2010. How can tax authorities collect outstanding payments more efficiently? Novel research by RWI in cooperation with the Australian National University provides new insights: based on three natural field experiments, the researchers show that a simplified language and reminders increase tax compliance by corporate taxpayers. Early reminders are especially attractive from a tax collector's perspective.
Keywords: 330